Study on Extraction and Purification of Acanthopanax senticosus Polyphenols by an Ionic Liquid-Assisted Aqueous Two-Phase System - Ying Li; Xiaoli Li; Xueyan Wang; Jiaojiao Xue; Rui Zhang; Yi Ding; Xiuling Chu; Jianqing Su (Molecules, 2023)
This study aimed to extract and purify polyphenols from Acanthopanax senticosus. A new green method was developed, in which ionic liquids (ILs) were used as aqueous two-phase (ATP) adjuvants to extract the polyphenols from A. senticosus. An ionic liquid-assisted aqueous two-phase system (IL-ATPS) was established. The purification of the polyphenols from the extraction fluid by AB-8 macroporous resin was conducted, and the kinetic mechanisms were studied. The reuse of ionic liquids was executed. The results showed that an [OMIM]Br-assisted ethanol/NaH2PO4 system (IL-ATPS) was the best extraction solvent. In this study, the following optimal extraction conditions were determined: 32 wt.% ethanol, 25 wt.% NaH2PO4, 9 wt.% additional ionic liquid, a solid–liquid ratio of 1:40 g/mL, an extraction temperature of 50 °C, a pH of 4.0, an extraction time of 50 min, and an extraction rate of the polyphenols at 15.90 mg/g. The optimum adsorption parameters of the macroporous resin AB-8 were as follows: a flow rate of 3.5 BV·h−1, a sample volume of 40 mL, an elution flow rate of 3.5 BV·h−1, an eluent volume of 80 mL, and an eluant that was constituted by an 85% volume fraction of ethanol. The decolorization effect of 4% activated carbon was better than the other amounts; in addition, a decolorization rate of 76.81% and an ionic liquid recovery rate of 81.12% were found to be the most optimal. Compared with the traditional extraction methods, IL-ATPS has the advantages of requiring simple operation, saving time, and high efficiency. In addition, it can be used for the extraction of the polyphenolic compounds.